The Role of Computer Aided Sketching Software (CAS) in Ideation Stages of Design - Hamid Reza Sharif; Negin Abdolahpoor Rafiei (صفه)
The importance of free-hand sketching on the one hand and the increasing use of computer software in various stages of the architectural design process on the other, havecaused controversies in the selection of appropriate design methods. Despite the increasing development of computers and computer-aided design software, the use of sketches in ideation stages is still common among designers. Today, various tools and software for computer aided sketching (CAS) have been marketed with the aim of closing the gap between ideation and the use of computers, so that the tendency of some designers, and more so students, to use them is evident. The purpose of this study was to investigate the possibility of replacing CAS with sketches and their impact on the designer's creative thinking for ideation. For this purpose, using descriptive-analytical method, the effect of sketches and CAS, as external influences in cognitive design skills are compared. The results show that although many efforts have been made to develop advanced application of CAS taking advantage of both sketching skills and technology, they have not yet managed to pose serious competitionfor hand sketches, and sketches have retained their advantages.